2016
DOI: 10.1186/s12940-016-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse weather conditions and fatal motor vehicle crashes in the United States, 1994-2012

Abstract: BackgroundMotor vehicle crashes are a leading cause of injury mortality. Adverse weather and road conditions have the potential to affect the likelihood of motor vehicle fatalities through several pathways. However, there remains a dearth of assessments associating adverse weather conditions to fatal crashes in the United States. We assessed trends in motor vehicle fatalities associated with adverse weather and present spatial variation in fatality rates by state.MethodsWe analyzed the Fatality Analysis Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…A previous study conducted for the nearby city of Riyadh also indicated that on average non-intersection crashes were more fatal compared to intersection crashes [59]. Similarly, the probability of low crash fatality on a rainy day having a large negative value for coefficient (β = −2.532) also appears conflicting to previous studies [60][61][62]. However, it can be argued from several previous studies that inclement weather may cause a significant reduction in vehicle speed [63][64][65].…”
Section: Crash Severity Modeling Using Logistic Regressionmentioning
confidence: 87%
“…A previous study conducted for the nearby city of Riyadh also indicated that on average non-intersection crashes were more fatal compared to intersection crashes [59]. Similarly, the probability of low crash fatality on a rainy day having a large negative value for coefficient (β = −2.532) also appears conflicting to previous studies [60][61][62]. However, it can be argued from several previous studies that inclement weather may cause a significant reduction in vehicle speed [63][64][65].…”
Section: Crash Severity Modeling Using Logistic Regressionmentioning
confidence: 87%
“…It is well known that bad weather can influence the occurrence of RTIs in various ways: it decreases the visibility of the host, increases the reaction time and braking distance of the agent and affects the immediate environment, particularly road surfaces. 5 22 According to the US Department of Transportation, fog can inhibit the abilities and visibility of drivers as well as the traction and stability of cars, thus heightening the risk of traffic collisions. 23 While it has not been demonstrated that speeding in cloudy/foggy conditions increases the risk of traffic collisions and RTIs, it has been found that even drivers who follow the speed limit are more vulnerable to crashes in poor weather conditions and other adverse circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly in terms of the road surface quality, most of the studies (n = 7) conducted in several countries like Saudi Arabia, US, Mexico, China, Canada and India reported that wet road surface significantly caused road accident [5][6][7][8][9][10][11]. Apart from that, slippery road has been reported to lead the accident causation especially in US and several other countries like Finland, Malaysia and Iran [10,[12][13][14][15][16]. Moreover, three studies conducted in China and a study conducted in Malaysia reported that asphalt-paved road with smoother surface is also prone to cause road accident [17][18][19][20].…”
Section: Road Faultymentioning
confidence: 99%
“…Secondly, in terms of road condition, most of the studies (n = 10) reported that driving on dark lighting road or road with no street light can significantly cause road accident in several countries like Saudi Arabia, China, Thailand, Pakistan and the US [5,6,8,16,20,[24][25][26][27][28]. Besides, nine included studies reported that the absence of road marking and other road signs as well as alert system such as the sign of speed limit have been reported to cause the occurrence of road accident [17,20,[24][25][26][27][28][29][30].…”
Section: Road Faultymentioning
confidence: 99%